The Principal's Leadership in Implementing the Merdeka Curriculum at MA Mu'allimin NW Pancor - Junaidi, Junaidi; Al Idrus, S. Ali Jadid; Bahtiar, Bahtiar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study investigates the role of principal leadership in implementing the Merdeka Curriculum at Madrasah Aliyah Mu'allimin NW Pancor. The Merdeka Curriculum represents a paradigm shift in Indonesian education, emphasizing learner autonomy and local content relevance. The research aims to explore how principal leadership influences the successful implementation of this curriculum. A qualitative approach was employed, utilizing a case study design. Data were collected through interviews with the principal, teachers, and key stakeholders involved in curriculum implementation. Additionally, document analysis of school policies and curriculum documents was conducted to provide contextual understanding. The data were analyzed thematically, focusing on identifying patterns and themes related to principal leadership behaviors, challenges encountered, and strategies employed to overcome them. Findings indicate that effective principal leadership, characterized by vision setting, support provision, and stakeholder collaboration, significantly facilitates curriculum implementation success. In conclusion, the study underscores the pivotal role of principal leadership in driving educational reforms such as the Merdeka Curriculum. The implications suggest the need for continuous professional development for principals and educators to enhance leadership capacity and ensure sustainable curriculum implementation.